Predictive Value of Non-Invasive Intracranial Pressure Monitoring in Profoundly Impaired Traumatic Brain Injury Patients - Barkah Waladani; Putra Agina Widyaswara Suwaryo; Isma Yuniar; Podo Yuwono; Endah Setianingsih (Babali Nursing Research, 2023)
Introduction: Trauma brain injury is an emergency condition that requires immediate precise first aid to reduce mortality rates and prevent secondary complications. Severe head injuries can lead to intracranial bleeding, thereby affecting hemodynamics. Monitoring the increase in intracranial pressure aims to mitigate the severity of head injury in patients, reducing deaths caused by brain edema. The significance of assessing the Glasgow Coma Scale (GCS) in relation to increased intracranial pressure is to determine conditions that could exacerbate physiological conditions due to head injury. The objective of this study is to determine changes in intracranial pressure among severe head injury patients. Methods: This research employs a descriptive study with a retrospective approach. Patient data were sourced from medical records of individuals treated at RS PKU Muhammadiyah Gombong, diagnosed with severe head injuries during the last year from January to December 2022. A total of 180 severe head injury patients' data were collected. Results: Research findings reveal that patients with head injuries experienced an increase in systolic blood pressure (33.3%), a decrease in pulse rate (30.5%), and a temperature within the normal range (78.9%). Conclusion: However, not all severe head injury patients exhibited elevated blood pressure, reduced pulse rate, or decreased oxygen saturation. All head injury patients experienced a decreased level of consciousness with a GCS score of less than 8.